Academic Procrastination of Undergraduates: Self-determination Theory and Academic Motivation - Cavusoglu, Ceyda; Karatas, Hakan (KAMLA-RAJ ENTERPRISES, 2015)
Procrastination is a common issue amongst university students. There are researches claiming that procrastination causes stress, high anxiety and illness, and in addition to that some researchers state that procrastination is negatively related to self-esteem. The purpose of this study was to investigate the relation between academic motivation, basic psychological needs and academic procrastination with respect to self-determination theory on undergraduate students from different departments. In order to collect data, three different scales (Tuckman's Academic Procrastination Scale, Vallerand's Academic Motivation Scale and Deci and Ryan's Basic Psychological Scale) have been used. The participants consist of 583 undergraduate students from different fields of study. Structural Equation Modeling (SEM) is used in order to analyze the data collected to test the hypothesis model. As a result, this study revealed that procrastination behavior is predictable through academic motivation and basic psychological needs. Also, academic motivation is predictable through basic psychological needs.
Keywords: Academic Procrastination; Self-determination Theory; Basic Psychological Needs; Academic Motivation; SCHOOL; EFFICACY; BEHAVIOR; FLOW; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics